The Influence of Teamwork on the Competitive Performance of Riverside Forest FC in the West Java Liga 4 Competition - Agustian Ngurah Paturusi; Komarudin Komarudin; Nidaul Hidayah (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Teamwork is a fundamental factor in achieving success in sports competitions, particularly in football, where effective coordination, communication, and collaboration among team members are essential for optimal performance. However, empirical evidence regarding the influence of teamwork on club performance at the regional competition level remains limited. This study aimed to examine the effect of teamwork on the competitive performance of Riverside Forest FC in the West Java Liga 4 competition. A quantitative study with a correlational approach was employed using a survey method. The study involved 30 respondents, consisting of athletes, coaches, managers, and club officials of Riverside Forest FC, selected through a total sampling technique. Data were analyzed using simple linear regression with SPSS software. The results revealed that teamwork had a significant positive effect on the club's competitive performance (β = 0.382; p < 0.001). The coefficient of determination indicated that teamwork explained 45.8% of the variance in competitive performance (R² = 0.458), while the remaining 54.2% was influenced by other factors outside the scope of this study. These findings demonstrate that effective teamwork, characterized by strong communication, coordination, mutual trust, and clear role distribution, plays a crucial role in enhancing the competitive performance of Riverside Forest FC in the West Java Liga 4 competition. Therefore, strengthening teamwork should become a strategic priority for football clubs seeking sustainable competitive success.